Game-Changer Using Dick and Carey Model in Enhancing Academic Achievement through Effective Instructional Strategies - Adeoye, Moses Adeleke; Wirawan, Kadek Adrian Surya Indra; Pradnyani, Made Shania Satya; Septiarini, Nyoman Intan (Universitas Pendidikan Ganesha, 2024)
Based on the results of interviews and observations carried out at school, it shows that the cognitive science learning outcomes of fifth grade elementary school students are still low. This research aims to analyze the significant influence of the discovery learning learning model assisted by mind mapping media on the cognitive science learning outcomes of fifth grade elementary school students. This research uses a quasi-experimental design with a non-equivalent control group design. The research population is 186 students, the sample determination will be random, and the experimental and control classes will be given a pretest and then equalized using the ANOVA test. The data collection method in this research is a test method, namely an objective test. There are two data analysis techniques in this research, namely descriptive statistical analysis and inferential statistical analysis. It is known that the t-calculated value of 24.448 is greater than the t-table of 1,681. This value shows that there is a significant influence of the discovery learning model assisted by mind mapping media on the cognitive science learning outcomes of fifth grade elementary school students. The practical implications of this research can be used by teachers as a reference in improving student learning outcomes.